Combining ability analysis for yield and it’s contributing characters in Indian mustard: Combining ability analysis for yield and it’s contributing characters in Indian mustard - S. R. KAMDI; P. D. RAUT; BEENA NAIR; A. D. SAPKAL; DIKSHA TAJANE; S. S. BHURE (Journal of Oilseeds Research, 2023)
Fifteen F1 crosses of Indian mustard [Brassica juncea (L.) Czern & Coss] obtained by half diallel fashion using six parents (excluding reciprocal) and evaluated along with parents and checks to study the combining ability. The parent NRCHB-101 and Pusa Mustard-31 were recorded as good general combiners for seed yield and it attributing characters. The crosses NRCHB-101 × Pusa Mustard-31 and Pusa Mustard-31 × Kranti both showed significant negative SCA effects for seed yield and most of its contributing characters and also exhibited significant mean for most of yield contributing characters. These crosses can be forwarded to next generation for producing genotypes of inherent superiority by blending and mixing maximum favorable following by simple selection methods.